The Roles of Islamic Educational Institutions in Religious Moderation - Muhammad Idris; Alven Putra (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Indonesia is a country which is rich in differences in ethnicity, race, skin color, and religion. Islamic education institutions, as part of many other institutions, must show their existence in dealing with differences through fostering religious moderation among students. This study aims at revealing the participation of Islamic education institutions in religious moderation and what Islamic educational institutions do to build religious moderation in Indonesia. This study uses a descriptive method with a library research approach. In so doing, this study is conducted by reading various references related to the discussed issues. The findings uncover that Islamic educational institutions have several roles in terms of religious moderation, namely: first, educational institutions have a role in formulating or revising educational goals; second, educational institutions have a role in providing guidance through educators; third, educational institutions have a role in synergizing religious moderation with materials/curriculum and learning processes; and fourth, educational institutions have a role in making students familiar with the applications of religious moderation through the school environment. The things that Islamic education institutions can do towards religious moderation are: first, formulating educational goals based on religious moderation; second, direct coaching through teachers; third, the integration of religious moderation in materials/curriculum in learning subjects; and fourth, synergizing all school members in habituating religious moderation behavior